FDG-PET/CT tumor to liver SUV ratio (TLR), tumor SUVmax, and tumor size: can this help in differentiating squamous cell carcinoma from adenocarcinoma of the lung? - Amr Muhammad Abdo Salem; Laila Hosny Hussein; Ahmed M. Osman (The Egyptian Journal of Radiology and Nuclear Medicine, 2022)
Abstract Background PET/CT plays an essential role in the diagnosis, staging, and follow-up of lung cancer. We aimed to assess the ability of PET/CT to differentiate between adenocarcinomas (AC) and squamous cell carcinomas (SCC) of the lung using tumor size, tumor maximum standardized uptake value (SUVmax), lymph nodes SUVmax, and tumor to liver SUV ratio (TLR). Results A total of 60 patients pathologically proved to have non-small cell lung cancer either AC or SCC were retrospectively evaluated. The mean tumor size, SUVmax of the tumor, and TLR were significantly higher in SCC lesions compared to AC lesions. The mean SCC tumoral size was 7.96 ± 2.18 cm compared to 5.66 ± 2.57 cm in AC lesions (P = 0.008). The mean tumor SUVmax in SCC lesions was 18.95 ± 8.3 compared to 12.4 ± 7.55 in AC lesions (P = 0.04). While the mean TLR of SCC lesions was 10.32 ± 4.03 compared to 7.36 ± 4.61 in AC lesions (P = 0.028). All three parameters showed the same sensitivity (75%), while TLR showed the highest specificity (77.78%) followed by tumor size (76.47%) and then SUVmax of the tumor (72.22%). Conclusions SCC of the lung has a higher mean tumor size, SUVmax of the tumor, and TLR as compared to AC which can be helpful tools in differentiation between them using PET/CT.